A Compact Representation for 3D Animation Using Octrees and Affine Transformations - Youyou Wang; Guilherme N. DeSouza (International Journal of Digital Multimedia Broadcasting)
This paper presents a new and compact 3D representation for nonrigid objects using the motion vectors between two consecutive frames. Our method relies on an Octree to recursively partition the object into smaller parts. Each part is then assigned a small number of motion parameters that can accurately represent that portion of the object. Finally, an adaptive thresholding, a singular value decomposition for dealing with singularities, and a quantization and arithmetic coding further enhance our proposed method by increasing the compression while maintaining very good signal-noise ratio. Compared to other methods that use tri-linear interpolation, Principle Component Analysis (PCA), or non-rigid partitioning (e.g., FAMC) our algorithm combines the best attributes in most of them. For example, it can be carried out on a frame-to-frame basis, rather than over long sequences, but it is also much easier to compute. In fact, we demonstrate a computation complexity of Θ(𝑛2) for our method, while some of these methods can reach complexities of 𝑂(𝑛3) and worse. Finally, as the result section demonstrates, the proposed improvements do not sacrifice performance since our method has a better or at least very similar performance in terms of compression ratio and PSNR.